Sense of mastery in first-episode psychosis—a one-year follow-up study - Lindgren, Maija; Therman, Sebastian; From, Tiina; Hietala, Jarmo; Laurikainen, Heikki; Salokangas, Raimo K. R.; Suvisaari, Jaana (Frontiers in Psychiatry, 2023)
A sense of mastery refers to beliefs about having control over one’s life and has been found to protect health and buffer the effect of stressful experiences. We investigated sense of mastery in first-episode psychosis (FEP) patients and population controls at baseline and at one-year follow-up. Pearlin and Schooler’s Sense of Mastery scale was completed by 322 participants at baseline and by 184 participants at follow-up. People having experienced FEP reported lower mastery than controls at both time points, but a modest increase was seen in patients at follow-up. The strongest correlates of high baseline mastery in FEP were lower depressive symptoms and higher perceived social support, whereas positive or negative psychotic symptoms did not associate with mastery. Current depressive symptoms also correlated with mastery at the follow-up point, and change in depressive symptoms correlated with change in mastery. Higher mastery at treatment entry predicted remission of psychotic symptoms one year later. Sense of mastery was also found to mediate the association of perceived social support with depressive symptoms. The usefulness of mastery measures should be further tested for estimations of patient prognosis in early psychosis.